Targeted interventions for improved equity in maternal and child health in low- and middle-income settings: a systematic review and meta-analysis. - Mats Målqvist; Beibei Yuan; Nadja Trygg; Katarina Selling; Sarah Thomsen (PLoS ONE)
Background Targeted interventions to improve maternal and child health is suggested as a feasible and sometimes even necessary strategy to reduce inequity. The objective of this systematic review was to gather the evidence of the effectiveness of targeted interventions to improve equity in MDG 4 and 5 outcomes. Methods and findings We identified primary studies in all languages by searching nine health and social databases, including grey literature and dissertations. Studies evaluating the effect of an intervention tailored to address a structural determinant of inequity in maternal and child health were included. Thus general interventions targeting disadvantaged populations were excluded. Outcome measures were limited to indicators proposed for Millennium Development Goals 4 and 5. We identified 18 articles, whereof 15 evaluated various incentive programs, two evaluated a targeted policy intervention, and only one study evaluated an intervention addressing a cultural custom. Meta-analyses of the effectiveness of incentives programs showed a pooled effect size of RR 1.66 (95% CI 1.43-1.93) for antenatal care attendance (four studies with 2,476 participants) and RR 2.37 (95% CI 1.38-4.07) for health facility delivery (five studies with 25,625 participants). Meta-analyses were not performed for any of the other outcomes due to scarcity of studies. Conclusions The targeted interventions aiming to improve maternal and child health are mainly limited to addressing economic disparities through various incentive schemes like conditional cash transfers and voucher schemes. This is a feasible strategy to reduce inequity based on income. More innovative action-oriented research is needed to speed up progress in maternal and child survival among the most disadvantaged populations through interventions targeting the underlying structural determinants of inequity.